2011
DOI: 10.4049/jimmunol.1100806
|View full text |Cite
|
Sign up to set email alerts
|

Serglycin: A Structural and Functional Chameleon with Wide Impact on Immune Cells

Abstract: Among the different proteoglycans expressed by mammals, serglycin is in most immune cells the dominating species. A unique property of serglycin is its ability to adopt highly divergent structures, because of glycosylation with variable types of glycosaminoglycans when expressed by different cell types. Recent studies of serglycin-deficient animals have revealed crucial functions for serglycin in a diverse array of immunological processes. However, its exact function varies to a large extent depending on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
134
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 135 publications
(136 citation statements)
references
References 62 publications
(74 reference statements)
0
134
0
2
Order By: Relevance
“…TNF), and anionic proteoglycans of serglycin type and various MC-specific proteases, the latter including tryptases, chymases, and carboxypeptidase A3 (2)(3)(4). Previous studies have shown that serglycin proteoglycan has a key regulatory role in maintaining the homeostasis of the secretory granules by forming complexes with the various granule proteases and bioactive amines, thereby promoting their storage within granules (5,6).…”
Section: Mast Cells (Mcs)mentioning
confidence: 99%
“…TNF), and anionic proteoglycans of serglycin type and various MC-specific proteases, the latter including tryptases, chymases, and carboxypeptidase A3 (2)(3)(4). Previous studies have shown that serglycin proteoglycan has a key regulatory role in maintaining the homeostasis of the secretory granules by forming complexes with the various granule proteases and bioactive amines, thereby promoting their storage within granules (5,6).…”
Section: Mast Cells (Mcs)mentioning
confidence: 99%
“…it is composed of a "core protein" to which highly sulfated and thereby negatively charged polysaccharides of glycosaminoglycan type are attached (1,2). Serglycin is a major component of secretory granules in many hematopoietic cell types (3-7) but has additionally been detected as a secretory product of non-hematopoietic cells (8).…”
mentioning
confidence: 99%
“…The storage and activities of MC proteases are, to a large extent, influenced by serglycin (Pejler et al , 2009a ;Kolset and Pejler , 2011 ), a proteoglycan species composed of a small protein core to which strongly negatively charged side chains of heparin (or chondroitin sulfate) type are attached. Primarily, serglycin proteoglycans are known to serve as storage matrices for several of the MC proteases, including mMCP-4, mMCP-5, mMCP-6 and MC-CPA, as shown by the absence of these proteases in MCs from serglycin-deficient mice ( Å brink et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%